Evaluasi Kesiapan Guru atau Pendidik Menghadapi Tantangan Generasi A untuk Meningkatkan Mutu Pendidikan di Era Kemajuan Teknologi - Timotius, Han; Dahliana Purba, Nursenta (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2023)
This study aims to examine the readiness of teachers or educators in facing the dynamics of Generation A (Alpha Generation) and its impact on enhancing the quality of education amidst technological advancements. The Alpha Generation represents the cohort born after the year 2010, growing up in a highly digitized and technologically advanced society. This research focuses on exploring the preparedness of educators to effectively engage and educate the Alpha Generation in order to improve educational outcomes. The study employs qualitative research methods to gather data on the challenges faced by teachers in adapting to the unique learning needs and preferences of Generation A. Additionally, the study investigates the strategies and approaches employed by educators to leverage technology as a tool for enhancing the quality of education. The findings of this research will contribute to a better understanding of the role of teachers in meeting the educational needs of Generation A and provide insights into the necessary competencies and skills required to ensure successful educational outcomes in the digital era.